Hubungan Pola Asuh Orang Tua dengan Perkembangan pada Anak Usia Pra Sekolah di TK Bustanul Athfal Banding Kecamatan Bringin Kabupaten Semarang - Dany Setiawan; Mona Saparwati; Umi Setyoningrum (Journal of Holistics and Health Science, 2020)
Development is a change and expansion in stages, the development of the stage of complexity from lower to higher, increasing and expanding one's capacity through growth, maturation and learning. One factor in child development is the caregiving environment. one of them is parenting is a description of the attitudes and behavior of parents and children in interacting, communicating during holding parenting activities and responding to their children's desires. The purpose of this research is to find out the correlation between parenting pattern and developments of preschool children at bustanul athfal kindergarten banding, bringin sub-diistrict of semarang regency. This type of research used a descriptive correlation research design and cross sectional time approach. The population in this study was 70. The sample in this study used a total sampling technique. From the results of this study parenting that is widely applied by parents is democratic parenting as many as 40 parents (57.1%) with normal child development of 38 (95.0%). From the chi-square test results obtained the correlation between parenting and development in pre-school age children in Kindergarten Bustanul Athfal Banding District of Bringin Semarang Regency with a P value = 0,000 means â‰¤ 0.5, it can be concluded that there is a correlation between patterns foster parents with development in preschoolers in Bustanul Athfal Kindergarten, Banding Village, Bringin District, Semarang Regency. Based on research parents should be able to provide effective care for children, because with effective care can provide opportunities for children to be competent in better development which is the provision of children in further development. ABSTRAK Perkembangan (development) adalah perubahan dan perluasan secara bertahap, perkembangan tahap kompleksitas dari yang lebih rendah ke yang lebih tinggi, peningkatan dan perluasan kapasitas seseorang melalui pertumbuhan, maturasi serta pembelajaran. Salah satu faktor dalam perkembangan anak yaitu lingkungan pengasuhan. salah satunya pola asuh orang tua merupakan gambaran tentang sikap dan perlaku orang tua dan anak dalam berinteraksi, berkomunikasi selama mengadakan kegiatan pengasuhan serta tanggapan terhadap keinginan anaknya. Tujuan dari penelitian ini untuk mengetahui hubungan pola asuh orang tua dengan perkembangan pada anak usia prasekolah di TK Bustanul Athfal Banding Kecamatan Bringin. Jenis penelitian ini menggunakan desain penelitian deskriptif korelasi dan pendekatan waktu cross sectional. Populasi dalam penelitian ini sejumlah 70. Sampel dalam penelitian ini menggunakan tehnik total sampling. Dari hasil uji chi-square diperoleh hasil adanya hubungan antara pola asuh orang tua dengan perkembangan pada anak usia pra sekolah di TK Bustanul Athfal Banding Kecamatan Bringin Kabupaten Semarang dengan nilai P value = 0,000 berarti â‰¤ 0,5. Orang tua hendaknya mampu memberikan pengasuhan yang efektif pada anak, karena dengan pengasuhan yang efektif mampu memberikan peluang pada anak untuk berkompetensi dalam perkembangan yang lebih baik yang merupakan bekal anak dalam perkembangan selanjutnya.